Clinical profile of duplex kidneys in children and its association with vesicoureteric reflux - Athiya Perveen K; Shirbin Joe Mathews; Thomas P Varghese (SpringerOpen, 2023)
Abstract Background Duplex kidney is a relatively common renal anomaly with a wide array of associations. With routine antenatal screening it is increasingly diagnosed these days. With this study, we aim to assess the clinical profile, prevalence of vesicoureteric reflux and highlighting the need for aggressive workup and management in selected cases to prevent further renal damage. Results Fifty-three children with duplex kidneys who attended the department of pediatric surgery at our institution from December 2016 to December 2021 were included in the study. The most common mode of presentation was urinary tract infection (58%). Fifty-three percent had an antenatally detected renal anomaly (out of these 46% were asymptomatic, 33% had UTI and 11% had other symptoms like straining, incontinence and abdominal mass). Sixty-one percent of patients were conservatively managed and 19 patients needed surgical intervention. Ureterocele was the most common condition necessitating surgery. Prevalence of vesicoureteric reflux was 60% and was comparable with other studies. Thirty-six percent of patients had renal scarring. Among the patients with scarring, 84% had VUR and 63% had febrile UTI. Conclusion Duplex kidney though a common congenital anomaly, requires a systematic evaluation to detect its various associations and a structured management protocol according to the associations. It has a high incidence of VUR which is a potentially hazardous condition which can affect the renal function if not evaluated and managed appropriately. Duplex can also be associated with obstructive conditions like PUJO, ureterocele, and ectopic megaureter which can cause rapid deterioration of renal function if not managed early enough. Though majority of the patients need only follow-up and antibiotic prophylaxis, there may be a certain sub group of patients who develop early scarring and need aggressive management. Our study aims to highlight the need to detect such patients early enough to reduce the morbidity.